The POWER OF COLLABORATION from ego-system to eco -system. - Gefen, Omri. ([S.l.] : PRODUCTIVITY PRESS, 2024)
Innovation has always been a core driver of growth at most organizations and collaboration is key to driving it. Collaboration facilitates the exchange of ideas and thoughts among team members who then weigh in on them with collective expertise.
Keywords: Cooperation; Strategic alliances (Business); BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Management